2012
DOI: 10.1111/j.1745-4557.2011.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

DETERMINATION OF THE QUALITY AND SHELF LIFE OF SOUS VIDE PACKAGED BONITO (SARDA SARDA, BLOCH, 1793) STORED AT 4 AND 12C

Abstract: The aim of this study was to determine the quality and shelf life of sous vide bonito stored at 4 and 12C. The total volatile basic nitrogen (TVB‐N) values of cold stored samples exceeded the recommended limit on 35th day of storage, while they were unacceptable according to sensory scores. The TVB‐N and trimethylamine‐N values of sous vide samples stored at 12C exceeded the limits at the 18th day, while sensory scores were very close to the acceptability limit. For all samples, mesophilic and psychrophilic ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 20 publications
6
12
0
Order By: Relevance
“…It was reported that, after 42 days of storage at 4 °C, the amount of TVB‐N in these sous vide fish products increased up to 410 and 320 mg N kg −1 for the control fillets and those dipped in lemon juice, respectively. Similar results were reported in sous vide vacuum packaged bonito fish fillets stored at different refrigeration temperatures . Turkkan et al .…”
Section: Resultssupporting
confidence: 84%
“…It was reported that, after 42 days of storage at 4 °C, the amount of TVB‐N in these sous vide fish products increased up to 410 and 320 mg N kg −1 for the control fillets and those dipped in lemon juice, respectively. Similar results were reported in sous vide vacuum packaged bonito fish fillets stored at different refrigeration temperatures . Turkkan et al .…”
Section: Resultssupporting
confidence: 84%
“…Thus, with SV cooking a product that is both savory, nutritious also has longer shelf life compared to standard products (Baldwin 2011). Many studies (Wang et al 2004;Diaz et al 2008;Mol et al 2012;Singh et al 2016;Hernández et al 2017) have been carried out to determine the shelf life of SV cooked products and studies showed that the shelf life can vary according to the properties of the product. Mol et al (2012) showed that the shelf life of the SV bonito, cooked at 70ºC for 10 min, was 28 days at 4ºC while 15 days at 12ºC.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies (Wang et al 2004;Diaz et al 2008;Mol et al 2012;Singh et al 2016;Hernández et al 2017) have been carried out to determine the shelf life of SV cooked products and studies showed that the shelf life can vary according to the properties of the product. Mol et al (2012) showed that the shelf life of the SV bonito, cooked at 70ºC for 10 min, was 28 days at 4ºC while 15 days at 12ºC. In another research Diaz et al (2008) stated that SV cooked pork loin was unacceptable after 10 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…This product has better color, flavor, texture and nutrient-retention characteristics compared with traditional cooking processes, representing an interesting alternative for consumption. Many studies have indicated the viability of using the sous vide process with different types of meat and fish (GALIMPIN-JOHAN et al, 2007;SHAKILA et al, 2009;MOL et al, 2012).…”
Section: Introductionmentioning
confidence: 99%